A 10 km time trial running bout acutely increases the number of angiogenic T cells in the peripheral blood compartment of healthy males. Issue 10 (13th September 2016) - Ross, Mark; Tormey, Peter; Ingram, Lesley; Simpson, Richard; Malone, Eva; Florida‐James, Geraint
New Findings: What is the central question of the study? Are CD31 + angiogenic T (TANG ) cells preferentially mobilized in response to acute exercise? What is the main finding and its importance? Our study reveals that TANG cells are redistributed into the circulation in response to acute strenuous exercise, but to a lesser extent than CD31 − T cells. Of the TANG cells mobilized, TANG cells expressing CXCR4 show greater redistribution compared with CXCR4 − TANG cells. Stromal‐derived factor 1‐α does not appear to play a role in the redistribution of TANG cells expressing CXCR4. The results suggest that a single bout of strenuous exercise might provide a short vasculogenic window, which could benefit the vascular system by redistributing CD31 + TANG cells. CD31 + T cells have been documented to possess vasculogenic properties and have been termed 'angiogenic T cells' (TANG cells). No study to date has fully characterized the effect of acute exercise on TANG cells. Twelve male participants aged 24–45 years undertook a running 10 km time trial, with peripheral blood samples taken before, immediately after and 1 h postexercise for quantification of TANG cells and subsequent CXCR4 cell surface expression by flow cytometry. The TANG cells demonstrated a 102% increase in number in the peripheral circulation immediately postexercise compared with pre‐exercise levels, followed by a large egress (50%) from the circulation in total TANG cells 1 h postexercise. This was due to changes in both CD4 + and CD8 + TANG cells, with CD8 + TANG cells displaying greater ingress (123%) and egress (52%) compared with CD4 + TANG cells (ingress, 83%; egress, 37%). The cell surface expression intensity of CXCR4 was affected only on CD8 + TANG cells, with a significant increase in cell surface expression immediately postexercise versus pre‐exercise levels. The CD31 − T cells displayed greater redistribution than CD31 + TANG cells (119 versus 102%). CXCR4‐expressing TANG cells showed greater response to acute exercise than CXCR4 − cells, which was accompanied by large changes in CXCR4 ligand SDF‐1α. The results show that acute exercise increases TANG cells in the circulation in response to an acute exercise stressor. Additionally, CXCR4 cell surface expression appears to be increased in response to exercise, which may result from the direct upregulation of CXCR4 on the T‐cell surface or could be due to CD31 + T cells being redistributed into the blood expressing greater levels of CXCR4. Abstract :